World Price Shocks, Income, and Democratization - Benjamin Zissimos (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper shows how a world price shock can increase the likelihood that democratization must be used to resolve the threat of revolution. Initially, a ruling elite may be able to use trade policy to maintain political stability. But a world price shock can push the country into a situation where the elite face a commitment problem that only democratization can resolve. Because the world price shock may also reduce average incomes, the model provides a way to understand why the level of national income per capita and democracy may not be positively correlated. The model is also useful for understanding dictatorial regimes' rebuttal of World Bank calls to keep their export markets open in the face of the 2007-08 world food crisis.
Keywords: D30; D74; F11; F13; P16; 330; democracy; institutions; price shocks; social conflict; trade policy